2011
DOI: 10.1007/s11408-010-0152-8
|View full text |Cite
|
Sign up to set email alerts
|

Underpricing and long-run performance of Chinese IPOs: the role of underwriter reputation

Abstract: Initial public offerings (IPOs), Underwriter reputation, Underpricing, Long-run performance, China stock market, G15, G32,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
1
7
0
1
Order By: Relevance
“…Ibbotson et al (1988) as well as Ritter (1991) had demonstrated in their study that IPOs have tendency to underperform in long term. The results were confirmed in other studies and markets as well (Chambers and Dimson, 2009;Loughran et al, 1994;Ritter and Welch, 2002;Su and Bangassa, 2011).…”
Section: Literature Reviewsupporting
confidence: 87%
“…Ibbotson et al (1988) as well as Ritter (1991) had demonstrated in their study that IPOs have tendency to underperform in long term. The results were confirmed in other studies and markets as well (Chambers and Dimson, 2009;Loughran et al, 1994;Ritter and Welch, 2002;Su and Bangassa, 2011).…”
Section: Literature Reviewsupporting
confidence: 87%
“…Chi and Padgett, 2005b; Cai et al ., 2008). Su and Bangassa (2011) argue that insufficient supply of and high demand for new issues and/or the previous record of large initial returns attract a great many investors in pursuit of the risk‐free profits of Chinese IPOs without concern for the quality of the IPO firms. Therefore, initial returns of IPOs are not an effective signal to predict the long‐run performance of Chinese IPOs.…”
Section: Cross‐sectional Results and Analysesmentioning
confidence: 99%
“…Guner, et al [27] and Jones [28] state that the underwriter factors are negative significant on initial return, supported by two other studies of Kenourgios [17] and Sharma, et al [29] with prestige variable, and also by Fung, et al [30] that states that the underwriter ranking effects negatively. However, two other studies found that underwriter factors have no significant effect on initial return, proposed by Almeida [31] and Su, et al [32].…”
Section: Hypothesis Of Prestigious Underwriters Beatty Andmentioning
confidence: 92%